Effects of Early Physical Therapy and Follow-Up in Acute Severe Coronavirus Disease 2019 Pneumonia: A Retrospective Observational Study - Bordas-Martínez, Jaume; Luzardo-González, Ana; Arencibia, Alejandro; Tormo, Franco; Matéu, Lluís; Vicens-Zygmunt, Vanesa; Bermudo, Guadalupe; Santos, Salud; Molina-Molina, María; Planas, Rosa; Suarez-Cuartín, Guillermo (Frontiers in Medicine, 2022)
Background: Rehabilitation in subjects with severe coronavirus disease 2019 (COVID-19) pneumonia has been widely recommended. However, data regarding the starting time of rehabilitation, subjects and healthcare workers safety, as well as, rehabilitation program features are limited. We aimed to assess the safety and characterize the effect of early and non-early physiotherapy on severe COVID-19 pneumonia subjects. Methods: Retrospective cohort study including a consecutive sample of surviving subjects admitted to an acute care hospital due to severe COVID-19 pneumonia from March 13th to May 15th of 2020. Subjects were separated into three groups: non-physical therapy, early physiotherapy (onset <7 days of admission), and non-early physiotherapy. Subject and therapist safety, and length of hospital stay were the main evaluated outcomes. Results: A total of 159 subjects were included (72% male; median age 62 years). Rehabilitation was performed on 108 subjects (32 early and 76 non-early physiotherapy). The length of hospital stay was 19 (IQR 36.25) and 34 days (IQR 27.25) (p=0.001) for early and non-early physiotherapy groups, respectively. No physiotherapist was infected and no subject adverse effect was identified. Multivariate analysis of subjects receiving physiotherapy during admission identified obesity (Odds ratio [OR] 3.21; p-value 0.028), invasive mechanical ventilation (OR 6.25; p-value <0.001) and non-early physiotherapy (OR 3.54; p-value 0.017) as independent factors associated with a higher risk of prolonged hospital stay. Survivors follow-up after hospital discharge at 8 weeks was completed by 54% of subjects. Conclusion: Rehabilitation in acute severe COVID-19 pneumonia is safe for subjects and healthcare workers, and could reduce the length of hospitalization stay, especially in those that may start early.